Baseline Study of Compliance of Antenatal Care Visits in The Working Area of The Majalaya Health Center, Bandung Regency - Virna Ghasyiyah; Tria Destiani Solihah (International Journal Of Health Science, 2024)
Since 2021, service standards for pregnant women have been aligned with guidelines from the World Health Organization (WHO), which recommend six antenatal visits during pregnancy—two in the first trimester, one in the second trimester, and three in the third trimester. This provision has been regulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 21 of 2021 concerning Health. This study aims to obtain a preliminary picture of the level of compliance of pregnant women in conducting pregnancy examination visits (Antenatal Care/ANC) in the working area of the Majalaya Health Center, Bandung Regency. This research used a descriptive method to describe the frequency distribution of compliance with ANC visits by pregnant women at the Majalaya Health Center. Based on the findings, the majority of pregnant women have not complied with the ANC visit schedule according to the recommended standards, with 31 respondents (58.5%) categorized as non-compliant. In terms of demographic characteristics, most respondents were in the age range of 20–35 years (49 respondents or 92.5%), had a secondary level of education (30 respondents or 56.6%), and had multigravida status (34 respondents or 64.2%). The level of compliance with ANC visits at the Majalaya Health Center is still relatively low, with more than half of the pregnant women failing to meet the standard number of visits. These findings suggest the need for targeted interventions to raise awareness of the importance of regular ANC visits for maternal and fetal health. Increasing education about the benefits of ANC, improving access to health facilities, and strengthening health workers’ roles in providing counseling could help enhance compliance rates. Furthermore, collaborative efforts between healthcare providers, families, and communities are essential to ensure that pregnant women receive optimal monitoring and care throughout their pregnancy.